Inferior Vena Cava Diameter is an Early Marker of Central Hypovolemia during Simulated Blood Loss. (20th April 2021) - Johnson, Blair D.; Schlader, Zachary J.; Schaake, Michael W.; O'Leary, Moragn C.; Hostler, David; Lin, Howard; St. James, Erika; Lema, Penelope C.; Bola, Aaron; Clemency, Brian M.
Abstract: Introduction: Inferior vena cava (IVC) diameter decreases under conditions of hypovolemia. Point-of-care ultrasound (POCUS) may be useful to emergently assess IVC diameter. This study tested the hypothesis that ultrasound measurements of IVC diameter decreases during severe simulated blood loss. Methods: Blood loss was simulated in 14 healthy men (22 ± 2 years) using lower body negative pressure (LBNP). Pressure within the LBNP chamber was reduced 10 mmHg of LBNP every four minutes until participants experienced pre-syncopal symptoms or until 80 mmHg of LBNP was completed. IVC diameter was imaged with POCUS using B-mode in the long and short axis views between minutes two and four of each stage. Results: Maximum IVC diameter in the long axis view was lower than baseline (1.5 ± 0.4 cm) starting at -20 mmHg of LBNP (1.0 ± 0.3 cm; p < 0.01) and throughout LBNP (p < 0.01). The minimum IVC diameter in the long axis view was lower than baseline (0.9 ± 0.3 cm) at -20 mmHg of LBNP (0.5 ± 0.3 cm; p < 0.01) and throughout LBNP (p < 0.01). Maximum IVC diameter in the short axis view was lower than baseline (0.9 ± 0.2 cm) at 40 mmHg of LBNP (0.6 ± 0.2; p = 0.01) and the final LBNP stage (0.6 ± 0.2 cm; p < 0.01). IVC minimum diameter in the short axis view was lower than baseline (0.5 ± 0.2 cm) at the final LBNP stage (0.3 ± 0.2 cm; p = 0.01). Conclusion: These data demonstrate that IVC diameter decreases prior to changes in traditional vital signs during simulated blood loss. Further study is needed to determine the view and diameter threshold that most accurate for identifying hemorrhage requiring emergent intervention.